Peran Ibu sebagai Orang Tua Tunggal dalam Mendukung Pendidikan Anak di Masa Pandemi Covid-19 - Fitri Qori Imami; Yosafat Hermawan Trinugraha; Abdul Rahman (Mahesa Research Center, 2021)
This research aims to identify and explain the role of mothers as single parents in providing educational support to children during the Covid-19 pandemic. The theory used in this research is structural functional theory by Talcott Parsons. This research method is qualitative with a case study approach. Data collection techniques used were interviews, observation, and documentation with triangulation of sources to test the validity of the data. Data analysis used data analysis from Miles and Huberman. The results show that the role of mothers as single parents in carrying out educational functions can run well, namely by providing educational support to children, especially during the Covid-19 pandemic, namely by accompanying children to study, helping children learn, reminding children to actively participate in classes and do their duties,meet learning facilities, and always provide motivation and advice to children. Single mothers also experience various obstacles, namely that they cannot fully and directly accompany their children when learning from home. In addition, single mothers also find it difficult to provide support to their children on their own, because children are sometimes difficult to manage. This happened because there was no father figure in the family.